Televidencias juveniles en Colombia: fragmentación generada por un consumo multicanal (2009)
The article looks at the more relevant findings of a study financed by the National Television Board, which was used to structure the programming for a project known as the National University Channel, now called Channel Zoom. The study sought evidence of fragmentation and segmentation in the television consumption habits of college students and high school juniors and seniors in eight provincial capitals throughout the country, and content preferences highly influenced by subscription-based television services or pay television, in which Colombia occupied the lead in Latin America at the time this article was written. The National University Channel is a Colombian television channel made available through the subscription- based television system.